We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
865
1
avatar

Suppose $a$ and $x$ satisfy $x^2 + \left(a-\frac{1}{a}\right)x  - 1 = 0$. Solve for $x$ in terms of $a$.

 Jan 22, 2018
 #1
avatar+101760 
+2

\($x^2 + \left(a-\frac{1}{a}\right)x - 1 = 0$\)

 

x =   [  - (a - 1/a )  ± √  [  ( a - 1/a)^2  - 4(1)(-1) ] ] /  2    simplify

 

x  = [ (1/a -a)  ± √ [  a^2 - 2   +  (1/a)^2  +  4]  ] / 2

 

x = [    (1/a - a ] ± √ [  a^2  + 2 +   1/a^2  ] ]  / 2

 

x  =  [  (1/a - a)  ± √  [  ( a + 1/a)^2 ]  ]  / 2

 

x  =  [ (1/a - a)  ±  (a + 1/a) ]  / 2

 

So  either       

 

x  = [  ( 1/a - a)  +  (a + 1/a) ] / 2  ⇒  (2/a)/2   =    1/a

 

Or

 

 x  =  [  (1/a  - a)  -   ( a + 1/a) ]  / 2  ⇒  ( -2a) / 2  =     - a

 

 

cool cool cool

 Jan 22, 2018

9 Online Users

avatar
avatar